2015
DOI: 10.1128/jvi.01972-15
|View full text |Cite
|
Sign up to set email alerts
|

Successive Respiratory Syncytial Virus Epidemics in Local Populations Arise from Multiple Variant Introductions, Providing Insights into Virus Persistence

Abstract: Respiratory syncytial virus (RSV) is a global respiratory pathogen of humans, with infection occurring characteristically as recurrent seasonal epidemics. Unlike influenza viruses, little attention has been paid to the mechanism underlying worldwide spread and persistence of RSV and how this may be discerned through an improved understanding of the introduction and persistence of RSV in local communities. We analyzed 651 attachment (G) glycoprotein nucleotide sequences of RSV B collected over 11 epidemics (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
77
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 54 publications
13
77
1
Order By: Relevance
“…Recent epidemiological reports have suggested that there may be virological interactions such as competition (234) between influenza virus and RSV infections (233,234). The early onset of an influenza season and the 2009 H1N1 influenza pandemic coincided with the delayed onset of RSV and hMPV epidemics (233,234). It was suggested that epidemiological studies such as these support a hypothesis of viral competition and/or virological interaction (234).…”
Section: Climate and Interactions Between Rsv And Other Viruses In Thmentioning
confidence: 93%
See 4 more Smart Citations
“…Recent epidemiological reports have suggested that there may be virological interactions such as competition (234) between influenza virus and RSV infections (233,234). The early onset of an influenza season and the 2009 H1N1 influenza pandemic coincided with the delayed onset of RSV and hMPV epidemics (233,234). It was suggested that epidemiological studies such as these support a hypothesis of viral competition and/or virological interaction (234).…”
Section: Climate and Interactions Between Rsv And Other Viruses In Thmentioning
confidence: 93%
“…In further support of a meteorological influence on respiratory viruses, RSV and influenza seasons occur at discordant times of the year in Australia, coinciding more with the rainy and winter seasons, respectively (229). Recent epidemiological reports have suggested that there may be virological interactions such as competition (234) between influenza virus and RSV infections (233,234). The early onset of an influenza season and the 2009 H1N1 influenza pandemic coincided with the delayed onset of RSV and hMPV epidemics (233,234).…”
Section: Climate and Interactions Between Rsv And Other Viruses In Thmentioning
confidence: 95%
See 3 more Smart Citations